Primary orthostatic tremor and orthostatic tremor‐plus in dogs: 60 cases (2003‐2020). (12th December 2021) - Liatis, Theofanis; Gutierrez‐Quintana, Rodrigo; Mari, Lorenzo; Czopowicz, Michał; Polidoro, Dakir; Bhatti, Sofie F. M.; Cozzi, Francesca; Tirrito, Federica; Brocal, Josep; José‐López, Roberto; Kaczmarska, Adriana; Cappello, Rodolfo; et al.
Abstract: Background: Orthostatic tremor (OT) is a rare movement disorder characterized by high‐frequency (>12 Hz) involuntary, rhythmic, sinusoidal movements affecting predominantly the limbs while standing. Objective: To describe the signalment, presenting complaints, phenotype, diagnostic findings, treatment, and outcome of a large sample of dogs with OT. Animals: Sixty dogs diagnosed with OT based on conscious electromyography. Methods: Multicenter retrospective case series study. Dogs were included if they had a conscious electromyography consistent with muscle discharge frequency >12 Hz while standing. Results: Fifty‐three cases were diagnosed with primary OT (POT). Giant breed dogs represented most cases (83%; 44/53). Most dogs (79%; 42/53) were younger than 2 years of age at onset of signs, except for Retrievers which were all older than 3.5 years of age. The most common presenting complaints were pelvic limb tremors while standing (85%; 45/53) and difficulty when rising or sitting down (45%; 24/53). Improvement of clinical signs occurred in most dogs (85%; 45/53) treated medically with phenobarbital, primidone, gabapentin, pregabalin or clonazepam, but it was mostly partial rather than complete. Orthostatic tremor‐plus was seen in 7 dogs that had concurrent neurological diseases. Conclusions and Clinical Importance: Primary OT is a progressive disease of young, purebred, giant/large‐breed dogs, which appears to begin later in life in Retrievers. Primary OT apparently responds partially to medications. Orthostatic tremor‐plus exists in dogs and can be concomitant or associated with other neurological diseases.